1995
DOI: 10.1104/pp.109.2.481
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 13NH4+ Efflux in Spruce Roots (A Test Case for Phase Identification in Compartmental Analysis)

Abstract: 111. Based on these findings and the assumption of an in-series arrangement of root cell compartments, it was concluded that phase 111 corresponded to the cytoplasm, phase II corresponded to the Donnan free space, and phase I corresponded to a film of solution adhering to the root surface.Efflux analysis is widely used to determine unidirectional ion fluxes, kinetic exchange constants of subcellular compartments, and ionic concentrations within compartments. In plants, compartmental analyses have been undertak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 34 publications
4
68
0
Order By: Relevance
“…We chose the duration of the loading period on the basis of the half-lives of exchange for the cytoplasmic compartment for NO 3 Ϫ in barley (compare below with Siddiqi et al, 1991). Therefore, 60 min of exposure to tracer ensured that cytoplasmic specific activity was Ն95% of that in the loading solution (Kronzucker et al, 1995e). After loading with 13 N, seedlings were transferred to efflux funnels (Siddiqi et al, 1991;Kronzucker et al, 1995b) and the roots were eluted with 20-mL aliquots of nonradioactive solution after varying time intervals.…”
Section: Caementioning
confidence: 99%
“…We chose the duration of the loading period on the basis of the half-lives of exchange for the cytoplasmic compartment for NO 3 Ϫ in barley (compare below with Siddiqi et al, 1991). Therefore, 60 min of exposure to tracer ensured that cytoplasmic specific activity was Ն95% of that in the loading solution (Kronzucker et al, 1995e). After loading with 13 N, seedlings were transferred to efflux funnels (Siddiqi et al, 1991;Kronzucker et al, 1995b) and the roots were eluted with 20-mL aliquots of nonradioactive solution after varying time intervals.…”
Section: Caementioning
confidence: 99%
“…Others have suggested that carbohydrate limitation may contribute to the toxicity syndrome, based on the finding that NH 4 ϩ per se is not translocated to the shoot in most plants (14), and, thus, all C skeletons for N assimilation must be provided in roots, causing local C deprivation (15). In some cases, external provision of ␣-ketoglutarate, a key carbon source for N assimilation, alleviated toxicity symptoms (4), but in other cases it failed to enhance NH 4 ϩ metabolism (16), suggesting that other factors may limit NH 4 ϩ assimilation. The hypothesis that NH 4 ϩ toxicity results from the uncoupling of photophosphorylation in chloroplasts (6) has long been shown to be incorrect, as even very large NH 4 ϩ concentrations do not affect this process in intact chloroplasts (17).…”
mentioning
confidence: 99%
“…Another major limitation is that at times, it can be difficult to discriminate between fluxes that are occurring across membranes and those occurring extracellularly. Such distinctions call for rigorous phase testing 7,10,20 . 10 , but from extracellular spaces (c.f., Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…as a function of elution time. For steady-state conditions, perform linear regressions and calculations of fluxes, half-lives of exchange, and pool sizes (for details, see [6][7][8][9] ). ).…”
Section: Compartmental Analysis By Tracer Efflux (Cate) Measurementmentioning
confidence: 99%
See 1 more Smart Citation